Imaging nucleation and propagation of pinned domains in few-layer Fe5–xGeTe2 - Hoegen, M; Fujita, R; Tan, AKC; Geim, A; Pitts, M; Li, Z; Stefan, L; Hesjedal, T; Atatuere, M (American Chemical Society, 2023)
Engineering nontrivial spin textures in magnetic van der Waals materials is highly desirable for spintronic applications based on hybrid heterostructures. The recent observation of labyrinth and bubble domains in the near room-temperature ferromagnet Fe5–xGeTe2 down to a bilayer thickness was thus a significant advancement toward van der Waals-based many-body physics. However, the physical mechanism responsible for stabilizing these domains remains unclear and requires further investigation. Here, we combine cryogenic scanning diamond quantum magnetometry and field reversal techniques to elucidate the high-field propagation and nucleation of bubble domains in trilayer Fe5–xGeTe2. We provide evidence of pinning-induced nucleation of magnetic bubbles and further show an unexpectedly high layer-dependent coercive field. These measurements can be easily extended to a wide range of magnetic materials to provide valuable nanoscale insight into domain processes critical for spintronic applications.